Civil Engagement Versus Personal Preference in Election: A Mixed Methods Study in the Indigenous Community of Kampung Naga - Yuliawati, Fitriyani; Sarofah, Riska (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyze the influence of civil engagement on the political preferences of the people in Kampung Naga during the 2024 regional head election process. Political preferences can reveal factors that influence a person's decision to participate in the regional head election. The study used a mixed method through the distribution of questionnaires and in-depth interviews with residents of Kampung Naga. The results showed that there was an influence between variables of 19%. This influence is very small. The researcher then studied it using a qualitative research approach. Some of the main reasons include traditional leaders who highly respect and give freedom to the community to choose, social changes in the form of modernization and changes in social values and access to various information such as social media. Factors such as personal preferences, family influences, and access to external information play a bigger role in shaping voter behavior. In the future, there needs to be further attention regarding social and cultural changes that can influence political behavior in traditional village communities.The recommendation in this study is to compare the implementation of elections in other indigenous communities in order to obtain comprehensive information regarding the influence of external culture and leadership on community behavior.